2019
DOI: 10.1177/1120700019877389
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcomes of total hip arthroplasty with a modular Birmingham head

Abstract: Introduction: Birmingham Hip Resurfacing (BHR) implants may be combined with a conventional femoral stem to create a modular metal-on-metal total hip arthroplasty (BHR MoM THA). There is little outcome data regarding this construct. This study examines midterm outcomes of BHR MoM THA compared to oxidised zirconium total hip arthroplasty (THA). Methods: A retrospective institutional review identified all patients receiving BHR MoM THA between April 2005 and February 2011 and a matched control cohort of zirconiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[ 3,4 ] Pairing CoCrMo alloys as articulating components of hip implants turned out to be unfavorable which is indicated by comparatively short primary implant survival strongly linked to the release of metallic nanoparticles and ions. [ 5‐8 ] The characteristics of local adverse effects highly depend on the elemental composition and physicochemical properties of the released particles. [ 9 ] Recently, it was shown that metal species are highly diverse in the peri‐implant membrane of metal‐on‐metal (MOM) hip implants.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3,4 ] Pairing CoCrMo alloys as articulating components of hip implants turned out to be unfavorable which is indicated by comparatively short primary implant survival strongly linked to the release of metallic nanoparticles and ions. [ 5‐8 ] The characteristics of local adverse effects highly depend on the elemental composition and physicochemical properties of the released particles. [ 9 ] Recently, it was shown that metal species are highly diverse in the peri‐implant membrane of metal‐on‐metal (MOM) hip implants.…”
Section: Introductionmentioning
confidence: 99%